Pengaruh Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Serta Implikasinya Terhadap Produktivitas Karyawan PT. Denso Indonesia Departemen Production Control dan Logistic - Sugiyanto Sugiyanto; Putri Cahyo Utami (Fakultas Ekonomi Universitas Borobudur, 2021)
This study aims to determine the extent of the influence of Service Quality, Sales Promotionon Customer Loyalty through Satisfaction Customers to GRABFOOD Customers in CawangUrban Village, Jakarta East. This research was conducted in August 2020– November 2020.The data used in this study are primary data collected from respondents' answers based onthe questionnaire given, namely as many as 100 samples. Methods of data processing usinganalytical methods path (Path Analysis) with the help of SPSS version 20.0. Statistical testingusing the individual parameter significance test (t test), coefficient test Determination andMediation Test with the help of Calculated By WarpPLS.The results showed that partially the 1: variable analysis service quality has a positive andsignificant direct effect on customer satisfaction, analysis 2: sales promotion variables have adirect effect positively and significantly towards customer satisfaction, analysis 3: variableservice quality has a positive and significant direct effect on customer loyalty, analysis 4: salespromotion variables have a direct effect positively and significantly towards customer loyalty,analysis 5: variables customer satisfaction has a positive and significant direct effect on customerloyalty, while analysis 6: service quality variables have an effect indirectly positively andsignificantly towards customer loyalty through customer satisfaction, and analysis 7: salespromotion variables indirectly positive and significant impact on loyalty customers throughcustomer satisfaction.Keywords: Service Quality, Sales Promotion, Customer Satisfaction and Customer loyalty.